Clinic pathogenetic characteristics of computer addiction - V. A. Soldatkin; D. C. Mavani; E. V. Karpova; A. Ya. Perekhov; V. V. Mrikhin; А. I. Kovalev; M. N. Kryuchkova; O. A. Bukhanovskaya; I. N. Khmaruk (Медицинский вестник Юга России, 2019)
Objective: sto study the clinical picture, psychopathological dynamics and significant pathogenetic factors of computer addiction development (CA).Materials and methods: the study included 93 patients with CA. The control group (CG) was represented by 50 healthy volunteers. Methods: clinical, psychological, paraclinical (brain MRI; EEG; daily excretion level of adrenaline, norepinephrine, dopamine; blood serotonin level; molecular genetic studies), statistical.Results: It is established, that the clinical picture of CA is represented by episodes of computer activity (CAct) and non-episode periods. Their features form a single syndrome of addiction to CAct. Increase of symptoms’ severity and their complication occur due to addition of the altered reactivity syndrome. The clinical-dynamic model of CA development is characterized by phasing with the presence of the initial stage and the stage of the expanded clinical picture. The disorder has a predisposition. The personality component of the predisposition includes the predominance of accentuations of unstable and schizoid types, low rates of internality in both groups. The morphofunctional component includes Val158Met polymorphism features of the COMT gene as predominance (59.1 %) of homozygotes for the Val allele and a high frequency of CNS structural anomalies (55 patients; 62.5 %). The gender component characterizes the predominance of males in CA. Some pathogenetic mechanisms of CA are established: impaired catecholamine and serotonin neuromediation, impaired bioelectrical brain activity with a high prevalence (47.0 %) of paroxysmal activity.Conclusions: Based on the identified pathogenetic mechanisms, the following approaches to the CA treatment are recommended: psychotherapy, psychopharmacotherapy, and their combination.